Short Communication: Sustainability of ecological dimension in peatland management in The Giam Siak Kecil Bukit Batu Landscape, Riau, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zulkarnaini, Sujianto, Wawan. 2022. Short Communication: Sustainability of ecological dimension in peatland management in The Giam Siak Kecil Bukit Batu Landscape, Riau, Indonesia. Biodiversitas 23: 1822-1827. The Giam Siak Kecil-Bukit Batu (GSKBB) in Riau Province, Indonesia, is assigned as a biosphere reserve due to its importance in terms of biodiversity conservation and ecosystem services provision, particularly due to the existence of large tracts of peat swamp forest. However, GSKBB landscape is threatened by various anthropogenic activities of using peatland resources because such activities are often carried out in an exploitative and destructive manner. This study aims to analyze the sustainability of the ecological dimension in peatland management in the GSKBB landscape. Methodologically, the design of this research used a mixed approach by combining quantitative and qualitative methods to determine the sustainability of peatland management. Primary data was collected through field observations and in-depth interviews with key informants from the GSKBB Biosphere Reserve management board, local government, private companies, non-governmental organizations (NGOs), and other local stakeholders. Computer programming RAPPEAT was used to analyze the sustainability index. The results of sustainability analysis of the ecological dimension of peatland management in the GSKBB landscape obtained a sustainability index of 46.5% or classified as less sustainable (